Tumor-infiltrating lymphocytes and tumor-associated macrophages as potential predictors of lymph node metastases in major salivary gland cancers - De Virgilio, Armando; Veneroni, Maria Vittoria; Costantino, Andrea; Festa, Bianca Maria; Fiamengo, Barbara; Sebastiani, Daniela; Spriano, Giuseppe; Di Tommaso, Luca (Frontiers in Medicine, 2023)
Purpose: To define if tumor-infiltrating lymphocytes (TIL) and tumor-associated macrophages (TAM) could represent potential predictors of lymph node metastases (LNM) in salivary gland cancers (SGC). Methods: A selected number of immunohistochemical markers related to TIL (CD3, CD4, CD68, FOXP3) and TAM (CD68, CD163) were investigated on major salivary gland cancers. TIL and TAM densities were measured on digital images using the open source QuPath both in the tumor interior (TI) and invasive margin (IM). Correlation with pathologic N classification and follow-up clinical data was investigated. Results: A total of 25 consecutive patients (males: 11; median age: 62.0) were included. Densities of CD3+ IM (OR = 7.7, 95% CI 1.2 – 51.2), CD8+ TI (OR = 7.7, 95% CI 1.2 – 51.2), CD8+ IM (OR = 7.7, 95% CI 1.2 – 51.2), FOXP3+ TI (OR = 24.0, 95% CI 2.2 – 255.9), CD68+ TI (OR = 7.7, 95% CI 1.2 – 51.2) and CD163+ IM (OR = 7.7, 95% CI 1.2 – 51.2), and the Immunoscore CD8/CD3 (OR = 1.9, 95% CI 1.1 – 3.4) were significantly associated with LNM (p < .05). CD3+ TI density was significantly associate with tumor recurrence and death (HR = 5.8, 95% CI 1.5 – 22.6; p < .05). Conclusions: A high density of specific TIL and TAM subpopulations might be correlated to a higher probability of LNM in SGC.